2019
DOI: 10.1111/1759-7714.13041
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine‐18‐fluorodeoxyglucose‐positron emission tomography evaluation in metastatic bone lesions in lung cancer: Possible prediction of pain and skeletal‐related events

Abstract: Background Fluorine‐18‐fluorodeoxyglucose‐positron emission tomography (FDG‐PET) uptake in primary lesions has been well studied, but little information is available about metastatic bone lesions in patients with lung cancer. The present study was performed to evaluate the relationships between metastatic bone FDG uptake and clinical parameters in patients with lung cancer. Methods FDG uptake was evaluated as the maximum standardized uptake (SUVmax) value of each target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Finally, we did not measure response in the bone, which can be problematic with current imaging techniques. 27…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not measure response in the bone, which can be problematic with current imaging techniques. 27…”
Section: Discussionmentioning
confidence: 99%
“…Gomi et al [25] reported that mean SUVmax of bone metastasis from lung cancer was 7.7. Whist in a study discriminating single-bone FDG lesions in lung cancer [26], a cutoff bone SUVmax of 4.3 was chosen with 81.8% sensitivity, 84.7% specificity, and 83.9% accuracy.…”
Section: Discussionmentioning
confidence: 99%